2015
DOI: 10.1007/s10064-015-0765-2
|View full text |Cite
|
Sign up to set email alerts
|

Soil–water retention curves and microstructures of undisturbed and compacted Guilin lateritic clay

Abstract: To investigate the soil-water retention curves of undisturbed and compacted lateritic clay specimens in the full suction range, suction is imposed or measured by using the pressure plate method, filter paper and vapor equilibrium technique with a saturated salt solution. The mercury intrusion porosimetry (MIP) tests were also performed to observe the pore size distribution (PSD) of undisturbed and compacted samples. The test results show that the undisturbed samples have lower gravimetric water content and deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…To simulate the working condition of the embankment, the test samples were prepared at a degree of compaction of 96% and an initial water content of 14%. First, the grains were fully mixed with distilled water, sealed with a film bag, and then placed in a moisturizer box for 48 h. Afterward, the grains were weighed and then poured into the direct shear ring cutters with inner diameters of 61.8 mm and heights of 20 mm as used by Sun et al [27] and Zhang et al [28] among others.…”
Section: Materials and Sample Preparationmentioning
confidence: 99%
“…To simulate the working condition of the embankment, the test samples were prepared at a degree of compaction of 96% and an initial water content of 14%. First, the grains were fully mixed with distilled water, sealed with a film bag, and then placed in a moisturizer box for 48 h. Afterward, the grains were weighed and then poured into the direct shear ring cutters with inner diameters of 61.8 mm and heights of 20 mm as used by Sun et al [27] and Zhang et al [28] among others.…”
Section: Materials and Sample Preparationmentioning
confidence: 99%
“…Other researchers in this area include Amanabadi et al [3], Sun et al [50], Liu et al [32], Shahnazari et al [47], and Kuang and Jiao [28]. Review previous research that has been done thus far [5,24,43,45,49,51,52,55,56] showed that no research had been conducted to compare the accuracy of the models in all soil texture categories and simultaneously in two categories eld's data and laboratory data.…”
Section: Introductionmentioning
confidence: 99%
“…The study of drying-wetting paths is a necessary step in the study of unsaturated soils behavior. Indeed, it has a double interest, on the one hand because it makes it possible to highlight the role of the suction to which the soil is subjected and to understand this important aspect of its behavior, on the other hand, many real phenomena follow, as a first approximation, drying-wetting paths (e.g., Al-Mahbashi et al, [2] Bendahgane et al, [5] Estabragh et al, [10] He et al, [15] Goual et al, [18] Seiphoori et al, [31] Sun et al, [33] Sun et al, [34] Tang et al, [35] and Wenjing et al [41] )…”
Section: Introductionmentioning
confidence: 99%